Analisis Kemampuan Literasi Matematika Siswa dengan Model PBL Berbantuan Google Classroom - Ervinayanti, Sevty; Mayasari, Novi; Ghoni Asror, Abdul (Galois: Jurnal Penelitian Pendidikan Matematika, 2023)
This study aims to describe students’ mathematical literacy abilities with the problem based learning model assisted by Google Classroom through classically and the improvement of students in the upper, middle and lower groups as well as the types of students errors in working on questions on Cartesian Coordinate material. This research method is descriptive qualitative with data collection namely observation, tests and interviews. The population of this study were students of class VIII-A of MTs Salafiyah Syafi’iyah Sukosewu with 3 subjects, namely the upper, middle and lower groups. The results of this study indicate that students with the Google Classroom assisted problem based learning model complete classically and there is an increase with the average value of the whole group, namely 70, the mathematical literacy ability of students in the upper group, namely being able to answer 4 out of 5 questions and students make mistakes in transforming problems, middle group students could answer 4 of 5 questions and students made mistakes in processing skills and lower group students could answer 2 of 5 questions and students made mistakes in understanding the problem, processing skills and writing answers. This study can be solved in accordance with the research objectives and the evidence that has been presented in the research result. ABSTRAK Penelitin ini bertujuan untuk mendeskripsikan kemampuan literasi matematika siswa dengan model problem based learning berbantuan Google Classroom tuntas secara klasikal dan peningkatan siswa kelompok atas, tengah dan bawah serta jenis kesalahan siswa dalam mengerjakan soal pada materi Koordinat Kartesius. Metode penelitian ini adalah kualitatif deskriptif dengan pengumpulan data yaitu observasi, tes dan wawancara. Populasi penelitian ini adalah siswa kelas VIII-A MTs Salafiyah Syafi’iyah Sukosewu dengan 3 subjek yaitu kelompok atas, tengah dan bawah. Hasil penelitian ini menunjukkan bahwa siswa dengan model problem based learning berbantuan Google Classroom tuntas secara klasikal dan ada peningkatan dengan nilai rata-rata keseluruhan kelompok yaitu 70, kemampuan literasi matematika siswa kelompok atas yaitu dapat menjawab 4 dari 5 soal dan siswa melakukan kesalahan transformasi masalah, siswa kelompok tengah dapat menjawab 4 dari 5 soal dan siswa melakukan kesalahan ketrampilan proses dan siswa kelompok bawah dapat menjawab 2 dari 5 soal dan siswa melakukan kesalahan memahami masalah, ketrampilan proses dan penulisan jawaban. Penelitian ini dapat disimpulkan bahwa dari masing-masing masalah dapat diselesaikan sesuai dengan tujuan penelitian serta bukti yang sudah dipaparkan pada hasil penelitian.